Is podocytopathy another image of renal affection in p-SLE? - Hend H. Abdelnabi (BMC, 2021)
Abstract Background Lupus podocytopathy (LP) is a renal affection described in systemic lupus erythematosus (SLE) patients with nephrotic range proteinuria, characterized by diffuse foot process effacement without immune deposits and glomerular proliferation. This study describes LP, its pathological features and outcomes of pediatric (p-SLE) patients in comparison to the usual lupus nephritis (LN) cases. Methodology A retrospective cohort study conducted on a 10-year registration (2010-2019) of 140 p-SLE patients at the Pediatric Department, Tanta University. Histopathological analysis with light microscopy (LM) and immunofluorescence (IF) of all renal biopsies were evaluated according to the International Society of Nephrology Renal Pathology Society (ISN/RPS) grading system. In addition, some biopsies were examined with electron microscopy (EM). Results Eighty-six p-SLE cases (61.4%) had renal involvement; seventy-nine biopsies (91.86%) of them met the classification criteria of LN as defined by ISN/RPS system. Five biopsies were normal (MCD) and two showed focal segmental sclerosis (FSGN) that did not meet any known classification of LN. Hence, they were reevaluated using EM that revealed diffuse effaced podocytes without glomerular sub-epithelial, endocapillary or basement membrane immune deposits, and were classified as having lupus podocytopathy, representing (8.14%) of all LN biopsies. Those seven cases showed good response to steroids with a complete remission duration of 3.40 ± 1.95 weeks. However, some case had 1-3 relapses during the duration of follow up. Conclusions LP is a spectrum of p-SLE, not an association as it is related to disease activity and its initial presentation.